Dynamic Behavior of Aggregated Buildings With Different Floor Systems and Their Finite Element Modeling - Stavroulaki, Maria E. (Frontiers in Built Environment, 2019)
The goal of this research is to propose a way of simulating the interaction between aggregated masonry buildings for the finite element analysis. Since in most cases the stiffness of the adjacent structure is difficult to evaluated due to unavailability of any data (unknown geometry, parameters, materials etc), a parametric study must be done in order to simulate the restrictions which are developed. In present paper first results of this research are presented via two different case studies where the rod elements or elastic foundations are proposed for the support of the adjacent structure. The natural frequencies of the real building complex are estimated by finite element modeling of all the structures and then they are used for the dynamic identification of the simplified model. The experimental measurements of the natural frequencies and modes of the building which is studied could be used for the dynamic identification of the finite element model.